The Behaviour Of LNAPL In Sand Due To Fluctuating Groundwater - Tan, Jin Sheng (Universiti Sains Malaysia, 2017)
Oil spill has been happening worldwide. The incidents of oil spillage can be happened during oil transportation, production and processing, as well as due to leakage of petroleum products from oil tankers. Even a minimal oil spill incidents happened, the soil properties will be altered or environment will be impacted with certain adverse effect. Oil which is lighter than water in density, tends to float on groundwater while they infiltrate into the ground. Thus, remediation work must be done to clean the contaminated soil by oil to prevent long term adverse effect on the environment or even humans upon consumption. Due to the difficulty and expensive tracing activity of oil spill in such huge area of soil, learning the fundamental of oil migration will facilitate the tracing and remediate contaminated soil effectively. Learning the behaviour of the oil or non-aqueous phase liquid (NAPL) migration in the soil due to its groundwater will allow us to study how the NAPL migrates in soil and distributes in groundwater. Hence, one-dimensional column test was carried out to study the behaviour of the NAPL migration in sand due to fluctuating groundwater. Fluctuating of groundwater will cause NAPL to redistribute and accumulate in the receded area. Despite the properties of NAPL which allow it floats or migrate along with groundwater table, certain amount of NAPL will be accumulated in area of groundwater receded. These can be observed through the saturation profile of NAPL and water in a sand sample.